Pengaruh Shopping Lifestyle dan Fashion Involvement Terhadap Impulse Buying Pada Pelanggan Distro Urban Traffic di Kota Medan - Yudha Maulana Putra; Wan Rizca Amelia; Alfifto Alfifto; Adelina Lubis (Universitas Medan Area, 2022)
Growth and developing of world fashion style makes public also get involved on purchasing of the products in marketplace. The purpose of this study was to determine the effect of shopping lifestyle and fashion involvement on impulse buying distro urban traffic customers in medan city. The type of research is quantitative research. The population of this research is the consumers of distro urban traffic in medan city, totaling 3584 visitors. The number of samples was 97 customers with the sampling technique using the slovin formula. The data used are primary data and secondary data. Primary data is obtained from questionnaires and interviews, secondary data is obtained from literature, previous research and so on. Data analysis technique using multiple linear regression. The results of this study indicate that simultaneously the variables shopping lifestyle and fashion involvement have a positive and significant effect on impluse buyinhg. The result of partial test shows that the variable shopping lifestyle have a positive significant effect on impulse buying and the variable fashion involvement have a positive significant effect on impulse buying. The result of koefisien determination shows the variable of shopping lifestyle and fashion involvement gained 68,9% on impulse buying.